Development of Biocalcium Production Process from Hybrid Catfish (Pangasianodon gigas × Pangasianodon hypophthalmus) Bone - Niwet, Jenjira; Mangumphan, Kriangsak; Daengprok, Wichittra; Leelapongwattana, Kittima; Yarnpakdee , Suthasinee; Senphan, Theeraphol (Burapha Science Journal, 2026)
Biocalcium from fish bones is a high quality of organic calcium product. The objective of this research was to develop a process for biocalcium production from hybrid catfish (Pangasianodon gigas x Pangasianodon hypophthalmus) bones including 4 steps: 1) high pressure water jet process 2) soaking in alkaline solution 3) ethanol immersion process and 4) bleaching and grinding to obtain biocalcium powder. %Yield, chemical composition, color values, lipid oxidation and the microstructure of all fish bone processes were analyzed. Obtained biocalcium had %yield of 14.46%. In addition, bio-calcium had a low protein, fat and moisture contents but increasing in ash content and the lightness values (L *) were observed (p ≤ 0.05). However, the process of ethanol immersion, bleaching and grinding to obtain biocalcium powder decreased in Thiobarbituric acid-reactive substances (TBARS) values (p ≤ 0.05) compared to the previous process. The particle sizes of biocalcium powder were in a range of 2-10 µm and distributed uniformly. Therefore, biocalcium production process of this study was suitable process to obtain a good quality biocalcium of fine powder, white color, without fishy and rancid odor. It can be developed as a calcium supplement in the further.